Transient Absorption Measurements on Anisotropic Monolayer ReS2. Issue 41 (28th August 2015) - Cui, Qiannan; He, Jiaqi; Bellus, Matthew Z.; Mirzokarimov, Mirzojamshed; Hofmann, Tino; Chiu, Hsin‐Ying; Antonik, Matthew; He, Dawei; Wang, Yongsheng; Zhao, Hui
Abstract : Anisotropic optical and transport properties of monolayer ReS2 fabricated by mechanical exfoliation are reported. Transient absorption measurements with different polarization configurations and sample orientations reveal that the absorption coefficient and transient absorption are both anisotropic, with maximal and minimal values occurring when the light polarization is parallel and perpendicular to the Re atomic chains, respectively. The maximal values are about a factor of 2.5 of the minimal values. By resolving the spatiotemporal dynamics of excitons, it is found that the diffusion coefficient of excitons moving along Re atomic chains is about 16 cm 2 s −1 at room temperature, which is about a factor of three larger than those moving perpendicular to that direction. An exciton lifetime of 40 ps is also extracted. These findings establish monolayer ReS2 as an anisotropic 2D transition metal dichalcogenide. Abstract : Transient absorption measurements establish monolayer ReS2 as an anisotropic 2D semiconductor. Both the linear absorption and transient nonlinear absorption are found to be a few times higher when the light polarization is along the Re atomic chain direction. Exciton diffusion is also found to be fast when moving along the Re atomic chains.